The refined method for calculating the volume of a silver vessel from the Maykop kurgan - Vodolazhskaya L.N. (Cultural Heritage and Modern Technologies, 2024)
This article describes a method for calculating the volume of a silver vessel "with a rosette" from the Maikop burial mound using a refined geometric model. It is concluded that the calculated volume is close to the upper limit of the volume of the large holes on the Pyatikhatki slab, and corresponds to the volume of the holes L11 and L12, which could serve to measure time between from 10 o'clock to 11 o'clock (10 a.m. - 11 a.m.) and from 11 o'clock to 12 o'clock (11 a.m. - 12 p.m.). Thus, the calculations using the refined model confirm the conclusion based on approximate calculations of the volume of the vessel body as a sphere, that the silver vessels from the Maykop kurgan could function as accumulative water clocks. And their volume corresponded to the volume of water for measuring one hour in the Mesopotamian metric tradition.